MOUTH DISSOLVING FILMS : A REVIEW - THAKUR SMRITI (International Journal of Pharma and Bio Sciences, 2013)
The purpose of current review is to enlighten the present and future prospective on Mouth dissolving film drug delivery system. Now a days, we observe padietric and geriatric patients facing the problem of dysphasia due to administration of monolithic solid dosage form, which are also seen in the case of fast dissolving tablets. Hence mouth dissolving film is proved to be better alternative in such cases. This fast dissolving drug delivery system is suited for the drugs which undergo high first pass metabolism and is used for improving bioavailability. Mouth dissolving film consists of thin oral strip; which release active ingredients immediately after uptake into oral cavity. These films have potential to deliver a drug systematically through intragastric, sublingual or buccal route of administration and also has been used for local action. The present review provides an account of various formulation considerations, method of preparation, and quality control of mouth dissolving films.